Effects of Easing LTV·DTI Regulations on the Debt Structure and Credit Risk of Borrowers - Meeroo Kim; Yoon Hae Oh (KDI Journal of Economic Policy, 2021)
With CB data in South Korea, this study examines whether the credit risk of borrowers changes when the regulation on bank mortgage supply is relaxed. We analyze the effect of deregulation on LTV and DTI limits in the Seoul-metropolitan area in August 2014 with a differencein-difference approach. We find that the probability of delinquency is lower in the Seoul metropolitan area after the deregulation than in other urban areas. The effect is noticeable among low-income and low-credit borrowers. We also find that borrowers change their debt structure to reduce the interest costs utilizing their improved access to bank mortgages. The findings suggest the necessity to consider the burden of the high interest costs of unsecured loans for debtors with low incomes and low credit ratings in designing housing finance regulations.
Keywords: G28; G51; 330; LTV; DTI; Mortgage Loan; Credit Risk